2009
DOI: 10.1021/es900305c
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Foliar Uptake and Within-Leaf Migration of Phenanthrene by Moss (Hypnum Cupressiforme) Using Two-Photon Excitation Microscopy with Autofluorescence

Abstract: Mosses have the potential to play a significant role in the global cycling and fate of semivolatile organic compounds (SVOCs), due to their extensive distribution at high latitudes and the long-range atmospheric transport of SVOCs. Unlike vascular plants mosses lack a substantial cuticle, vascular system, or root structure, taking up water, nutrients and SVOCs primarily from the atmosphere. Mosses have thus been effectively used as passive air samplers for many SVOCs in urban and rural locations. The potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 41 publications
1
20
0
2
Order By: Relevance
“…Lipophilic uncharged VOCs such as terpenes tend to be adsorbed within the hydrophobic cuticular wax layer upon gas deposition 40 , from where they may be taken up into the leaf through the stomata 41,42 . Limonene uptake and re-release by 13 plant species was reported by Noe et al ., (2008) 39 , with the uptake of the monoterpene scaling positively with leaf lipid content.…”
Section: Discussionmentioning
confidence: 99%
“…Lipophilic uncharged VOCs such as terpenes tend to be adsorbed within the hydrophobic cuticular wax layer upon gas deposition 40 , from where they may be taken up into the leaf through the stomata 41,42 . Limonene uptake and re-release by 13 plant species was reported by Noe et al ., (2008) 39 , with the uptake of the monoterpene scaling positively with leaf lipid content.…”
Section: Discussionmentioning
confidence: 99%
“…Keyte et al . 11 found that the penetration of phenanthrene (PHE), a typical persistent organic pollutant, was much faster through the surface of moss (which has no typical cuticle) than through that of a spinach leaf (which has a typical cuticle). The cuticle is an essential barrier that hinders the penetration of organic pollutants into the plant, but the contributions of cuticular components to such penetration remain unresolved.…”
mentioning
confidence: 99%
“…The contribution of root uptake for PAHs was only 2.4% in soil spiked with naphthalene, phenanthrene, and pyrene (Su and Zhu 2008). The PAHs in shoot were considered to accumulate from atmosphere directly other than transport from root (Su and Zhu 2008;Keyte et al 2009 Table 5 The loading matrix of partial least squares regression models for oat dissipation in rhizosphere soil was due to biodegradation or biotransformation (Binet et al 2000). This process would be influenced by partition coefficient of different PAHs between soil and root or between atmosphere and shoot.…”
Section: Discussionmentioning
confidence: 99%